2011
DOI: 10.1177/1744629511401168
|View full text |Cite
|
Sign up to set email alerts
|

The impact of training on teacher knowledge about children with an intellectual disability

Abstract: The present study examines the impact of a short training session on the knowledge of teaching staff in Scotland about children with an intellectual disability. Despite the majority of participants reporting that they had a child with an intellectual disability in their classroom, the initial level of knowledge concerning intellectual disability was low. This was partly considered to be due to terminology differences that exist between the health and education sectors and a lack of training specific to the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…This review classified the mode of course delivery into coursework and field experience: seven studies delivered the training content through coursework and the other six used a combination of coursework and field experiences. Two of the 13 studies involved follow-up activities in order to monitor the implementation (Wolery and Anthony 1997) and to request feedback on impact (Rae, McKenzie, and Murray 2011), while the other studies had no information about this.…”
Section: Educational Research 317mentioning
confidence: 99%
See 1 more Smart Citation
“…This review classified the mode of course delivery into coursework and field experience: seven studies delivered the training content through coursework and the other six used a combination of coursework and field experiences. Two of the 13 studies involved follow-up activities in order to monitor the implementation (Wolery and Anthony 1997) and to request feedback on impact (Rae, McKenzie, and Murray 2011), while the other studies had no information about this.…”
Section: Educational Research 317mentioning
confidence: 99%
“…Out of 10 studies, five measured the knowledge content. Two studies (Rae, McKenzie, and Murray 2011;Sari 2007) showed large effect sizes (more than 1) whereas Miller, Wienke, and Savage (2000) reported an effect size of 0.43. One other study, conducted by Edwards, Carr, and Siegel (2006), indicated effect sizes of 1.09 for a group of pre-service teachers and 0.37 for a group of in-service teachers.…”
mentioning
confidence: 99%
“…dyslexia, in the US. Many professionals and social care staff, including those employed in intellectual disability services, may lack a full understanding about what an intellectual disability is and the needs and characteristics of the heterogeneous group of people who have this diagnosis (McKenzie, Matheson, Patrick, Paxton, & Murray 2000;Rae, McKenzie, & Murray, 2011;Williams & McKenzie, 2009). It is perhaps, therefore, unsurprising that staff in the criminal justice system may also lack this knowledge (Scheyett, Vaughn, Taylor, & Parish, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen of the 21 quantitative studies used a repeated measures design with measurements taken at baseline and post intervention (Adler et al, 2005;Bailey, Barr, & Bunting, 2001;Freudenthal et al, 2010;Hall & Hollins, 1996;Iacono et al, 2011;Kobe & Mulick, 1995;Li & Wang, 2013;MacDonald & MacIntyre, 1999;Melville et al, 2006;Nosse & Gavin, 1991;Rae, McKenzie, & Murray, 2011;Rimmerman, Hozmi, & Duvdevany, 2000;Tracy & Iacono, 2008;Walker & Scior, 2013;Wong & Wong, 2008). One study provided baseline data for both the experimental and comparison group but did not report post-data for the comparison group (Nosse & Gavin, 1991).…”
Section: Overview Of Methodology and Reportingmentioning
confidence: 99%
“…(3) Obstacles: acknowledgement of hardship, financial strain; by Rae et al (2011) who evaluated training on diagnostic criteria and general information about intellectual disability on teaching staff's knowledge. The training increased knowledge scores and these improvements were sustained at one month follow-up.…”
Section: Interventions That Aimed To Increase Knowledge and Improve Amentioning
confidence: 99%